Potentiation of TRAP-6-induced platelet dense granule release by blockade of P2Y(12) signaling with MRS2395 - Mitrugno, Annachiara (Platelets, 2017)
The release of ADP from platelet dense granules and its binding to platelet P2Y(12) receptors is key to amplifying the initial haemostatic response and propagating thrombus formation. P2Y(12) has thus emerged as a therapeutic target to safely and effectively prevent secondary thrombotic events in patients with acute coronary syndrome or a history of myocardial infarction. Pharmacological inhibition of P2Y(12) receptors represents a useful approach to better understand the signaling mediated by these receptors and to elucidate the role of these receptors in a multitude of platelet hemostatic and thrombotic responses. The present work examined and compared the effects of four different P2Y(12) inhibitors (MRS2395, ticagrelor, PSB 0739 and AR-C 66096) on platelet function in a series of in vitro studies of platelet dense granule secretion and trafficking, calcium generation, and protein phosphorylation. Our results show that in platelets activated with the PAR-1 agonist TRAP-6 (thrombin receptor-activating peptide), inhibition of P2Y(12) with the antagonist MRS2395, but not ticagrelor, PSB 0739 or AR-C 66096, potentiated human platelet dense granule trafficking to the plasma membrane and release into the extracellular space, cytosolic Ca(2+) influx and phosphorylation of GSK3β-Ser9 through a PKC-dependent pathway. These results suggest that inhibition of P2Y(12) with MRS2395 may act in concert with PAR-1 signaling and result in the aberrant release of ADP by platelet dense granules, thus reducing or counteracting the anticipated anti-platelet efficacy of this inhibitor.